If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7x + -24 = 0 Reorder the terms: -24 + 5x + -7x = 0 Combine like terms: 5x + -7x = -2x -24 + -2x = 0 Solving -24 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -2x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -2x = 0 + 24 -2x = 0 + 24 Combine like terms: 0 + 24 = 24 -2x = 24 Divide each side by '-2'. x = -12 Simplifying x = -12
| 4d^2-16-8d-d^2=0 | | x^3-24x^2+180x-424=0 | | 3x-xln(x)-9=(-4) | | 48=5x-28 | | 5+7x=9x-12 | | Log(x)12=5 | | y*(-3-y)=-10 | | -3y-y=-10 | | 15y-y=56 | | 3x^2-6x+1.625=0 | | f(1/2x)*(1/2x) | | 681=X+0.3X | | (0.45*1.6x)+(0.55*x)=6 | | (14/120)x(14/120)x(14/120) | | (0.45*1.6x)+(0.55*x)=3 | | 4x-9=ax-3a | | 4x-9=ax-3ax | | 4x-9=ax-3 | | 54-12x=16x+10 | | (0.6*2x)+(0.4*x)=6 | | X^2+y^2=6z | | 2=-x-1 | | 1=-x-1 | | z^3=-81 | | 3=4-2y | | 1=4-2y | | 3(3x+2)=11x+4-2x+2 | | (1*2x)+(1*x)=12 | | (1.2*2x)+(0.8*x)=12 | | 2x(x+2)(x+6)=0 | | (1.2*2x)+(0.8*x)=6 | | Factorizem^3+5m^2=0 |